Nearly Self-Similar Pulse Compression in Horizontally Slotted Waveguides at 2.0 μm - Jiayao Huang; Feng Ye; Qian Li (IEEE Photonics Journal, 2024)
The picosecond pulse can be directly generated in the integrated mode-locked laser, which reduces the size of light source to the optical chip. However, it is still a challenge to directly generate femtosecond pulses in the integrated scheme. In this work, we theoretically propose nearly self-similar pulse compression in the silicon/silicon nitride horizontally slotted waveguides (Si-Si3N4 HSWs) that the femtosecond pulse can be acquired without assistance by active components. Our scheme consists of the single pulse compression, high-repetition-rate pulse train compression and two pulses combination and compression. For the single pulse compression, the input pulse can be compressed from 1 ps to 82.6 fs with a remarkable compression factor of 12.11. Moreover, we present a favorable approach of pulse parameter equations (PPEs), which provides the theoretical results in much shorter calculation time. Furthermore, we achieve the higher-peak-power pulse train compression and two pulses combination and compression in the same Si-Si3N4 HSWs, which accompanies with an impressive compression factor of 30.56 and 4.97. Eventually, self-similar pulse compression provides valid guidance for the integrated pulse compressor in the experimental endeavors.